2005
DOI: 10.1074/jbc.m407724200
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Phosphorylation and Modulation of Its E3 Ubiquitin Ligase Activity

Abstract: Mutations in the PARKIN Parkinson's disease (PD)1 is the second most common neurodegenerative disorder. Parkinsonian symptoms are caused by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (1). Although more than 90% of PD cases occur sporadically, the study of genetic mutations has offered great insight into the molecular mechanisms of PD (2). After the discovery that mutations in the PARKIN gene cause autosomal recessive juvenile parkinsonism (3), parkin mutations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 38 publications
3
89
0
Order By: Relevance
“…Based on the enhancement of UbcH7, UbcH8 and substrate binding (synphilin-1, Sept5, SIM2) in the presence of the IBR domain it is clear the T351P mutation would not only disrupt the binding site on the IBR domain surface but would spatially separate the RING1 and RING2 domains due to IBR unfolding. This idea, in combination with the Parkin IBR structure also agrees with the negative modulation of Parkin by either S-nitrosylation or phosphorylation (31)(32)(33). The only free thiol in the IBR domain (C323) a potential nitrosylation site, and the residue for phosphorylation (S378) are proximal to each other where the N and C termini meet near the edge of zinc site II.…”
Section: Parkin Ibr Forms a Dual Scissor-like And Gag Knuckle-like Stsupporting
confidence: 60%
“…Based on the enhancement of UbcH7, UbcH8 and substrate binding (synphilin-1, Sept5, SIM2) in the presence of the IBR domain it is clear the T351P mutation would not only disrupt the binding site on the IBR domain surface but would spatially separate the RING1 and RING2 domains due to IBR unfolding. This idea, in combination with the Parkin IBR structure also agrees with the negative modulation of Parkin by either S-nitrosylation or phosphorylation (31)(32)(33). The only free thiol in the IBR domain (C323) a potential nitrosylation site, and the residue for phosphorylation (S378) are proximal to each other where the N and C termini meet near the edge of zinc site II.…”
Section: Parkin Ibr Forms a Dual Scissor-like And Gag Knuckle-like Stsupporting
confidence: 60%
“…Parkin was shown to be phosphorylated in vivo at serines 101, 131, 136, and 296 by mass spectroscopy analysis (34). Ser-131 was found by the same authors to be phosphorylated in vitro by cAMP-dependent protein kinase.…”
Section: Discussionmentioning
confidence: 88%
“…For this, we first checked the levels of Parkin phosphorylation in the absence and presence of the phosphatase inhibitor okadaic acid, which was shown to increase Parkin phosphorylation levels (34). We found that the incubation with okadaic acid robustly increases the steady-state levels of Parkin phosphorylation in HEK 293 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations